KEPEMIMPINAN TRANSFORMASIONAL, TRANSAKSIONAL, MOTIVASI KERJA, DAN KINERJA PERSONEL SATUAN PROVOST DETASEMEN MARKAS MABES ANGKATAN LAUT - Lutfi Adin Affandi; Mohammad Rizan (Faculty of Economics, State University of Jakarta., 2015)
The study aimed to investigate the effect of transformational leadership, transactional leadership and work of motivation on performance of personnel (Y) provost detachment headquarter of Indonesian Navy, either simultaneously or partialy. 59 respondent from provost detachment headquarter of Indonesian Navy, completed 71 item self-reorted measures. The data collected survey and quesionares distributed to respondent. The statistic methode used was Multiple Regression. As expected, result indicated that transformational leadership, transactional leadership and work of motivation has positive effects on performance personnel. The result show that Fcount 26.154 is greater than Ftable 2.77 at significant level 0.05 then H0 is rejected, which means that the transformational leadership (X1), transactional leadership (X2) and work of motivation (X3) together-equally significant effect on performance of personnel (Y). Partial test, all the independent variables have a value of significant alpa below 0.05 or tcount independent variables is greater than ttables thus proving the influence of transformational leadership, transactional leadership and work of motivation partially on performance personnel.